(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article examines the development and implementation of effective mechanisms of interaction “preschool educational institution – microdistrict – school – family” in the education of youth in the local community.